PERHATIAN YESUS KEPADA ORANG SAMARIA DALAM INJIL SINOPTIK SEBAGAI WUJUD MISI-NYA KEPADA SEMUA BANGSA - L. M, Yusuf; Marriba, Narsing L. (Jurnal Teologi RAI, 2024)
Abstract: Jesus' attention to the Samaritans was one of the ways Jesus used to dismantle the paradigm of the disciples' Mission so that they would not only focus on their own ethnicity and nation but also see the Mission carried out by Jesus as a whole. This situation is very clearly explained by the apostle John in the Fourth Gospel, but in the Synoptic Gospels it is also clearly seen in several contexts. Jesus' intention was that the disciples could see the concept of the Gospel Message to other nations as a whole. Many views show that later at the peak of the Great Mandate as a form of a new command issued by Jesus to preach the Gospel to all nations. This is not wrong, but by looking long before that in Jesus' ministry several times in the Synoptic Gospels, he paid attention to the Samaritan ethnic group as representatives of other nations who had the right to the salvation carried out by Him. This was done by Jesus so that the disciples and all evangelists would not stop at their place to preach the gospel but must continue to understand that the tribes in the world who have not heard the gospel, they also have the same right to be saved. The PI movement must continue to produce repentant souls. The method used in the study is qualitative with a library research approach. The author collects data through primary sources such as books and articles that have been published both online and offline. Then the results of the research, the author provides conclusions related to Jesus' attention to the Samaritans as a strong foundation for actively carrying out the Mission to all tribes, languages ​​and nations. This mission basis must remain the main benchmark that is consistently maintained and implemented in the context of the Gospel Proclamation Mission Movement carried out by both Church Institutions, Mission Institutions and Theological Schools or Seminaries